(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The given article describes biosafety problems, which exist in our days, and also the readiness of the country to react and eliminate the consequences of biological hazards including protection of the population and a system of their life support and agriculture as well